Disparity In The Judge's Ruling About Community Property Disputes After Divorce (An Analysis of The Verdict In The South Jakarta Religious Court, Religious Court of Jakarta And Supreme Court) - Kamarusdiana Kamarusdiana (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract. There is a discretion in the South Jakarta Religious Court with the provisions of the Compilation of Islamic Law. Thus, the fundamental problem of legal theory and theory which is used by the Judge to decide upon the joint property, why the decision is different between the judges at the first level, the appeal and the cassation, and how the parties' argument in acquiring the common property. The result shows that the argument used by the panel of judges at the first level is in fact of the law property obtained from the income of the wife in addition to meet the sense of justice and benefit. While the judges at the higher level and Cassation in the Supreme Court are more normative to the existing of legal norms. The theoretical approach used by judges at the first level is the theoretical approach of legal realism while the judges at appeal level and Cassation use theories of legal positivism. Keywords: Joint Property, Legal Positivism, The Ijtihad Of Judges, The Disparity Of The Verdict. Abstrak. Terdapat ketidaksesuaian putusan mengenai pembagian harta bersama pada Pengadilan Agama Jakarta Selatan dengan ketentuan dalam Kompilasi Hukum Islam. Sehingga, yang menjadi permasalahan mendasar hukum dan teori apa yang digunakan oleh Hakim untuk memutus harta bersama tersebut, kenapa putusan tersebut berbeda antara hakim ditingkat pertama, banding dan Kasasi, serta bagaimana argumentasi para pihak dalam memperioleh harta bersama. Berdasarkan hasil penelitian penulis, Argumentasi yang digunakan majelis hakim ditingkat pertama ialah secara fakta hukum harta yang diperoleh lebih banyak dari hasil penghasilan isteri disamping untuk memenuhi rasa keadilan dan kemaslahatan. Sedangkan hakim ditingkat II (PTA) dan Kasasi di Mahkamah Agung lebih normatif kepada norma hukum yang sudah ada. Pendekatan teori yang digunakan oleh hakim ditingkat pertama lebih kepada pendekatan teori realisme hukum sementara hakim ditingkat banding dan Kasasi lebih banyak menggunakan teori positivisme hukum.Kata Kunci: Harta Bersama, Positivisme Hukum, Ijtihad Hakim, Disparitas Putusan. DOI: 10.15408/jch.v6i1.8266